Technology assessment for power quality mitigation devices - Micro-DVR case study - Vairamohan, Baskar; Komatsu, Wilson; Galassi, Mauricio; Monteiro, Thiago Costa; de Oliveira, Marco Antonio; Ahne, Se Un; Matakas, Lourenco; Marafão, Fernando Pinhabel [UNESP]; Bormio, Edison; de Camargo, Josue; McGranaghan, Mark F.; Jardini, Jose Antonio (Elsevier B.V. Sa, 2011)
This work presents a case study on technology assessment for power quality improvement devices. A system compatibility test protocol for power quality mitigation devices was developed in order to evaluate the functionality of three-phase voltage restoration devices. In order to validate this test protocol, the micro-DVR, a reduced power development platform for DVR (dynamic voltage restorer) devices, was tested and the results are discussed based on voltage disturbances standards. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Power quality; Power electronics; Technology assessment; Power conditioning; Voltage sags; Voltage swells